1999
DOI: 10.1007/pl00011747
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of a Mitochondrial DNA Control Region Fragment Amplified from Three Adriatic Flatfish Species and Molecular Phylogenesis of Pleuronectiformes

Abstract: : The 5'-end of the mitochondrial control region of three Pleuronectiformes from the Adriatic Sea, Platichthys flesus italicus (Adriatic flounder), Solea vulgaris (common sole), and Solea kleini (Klein's sole), was sequenced and compared with that of six other flatfish species from the families Pleuronectidae and Bothidae. The sequence structures of all flatfishes appear very similar and consist of alternate short segments with low, medium, and high rates of nucleotide substitution. Four conserved 19-bp repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…Paralichthyidae appeared divided into two groups, one group was constituted by the genera Paralichthys and Pseudorhombus (Paralichthyidae II), which were soundly related to the members of the family Pleuronectidae which were analyzed. A relationship between species of Pleuronectidae and several paralichthyid genera had been previously suggested by Tinti et al (1999), and Berendzen and Dimmick (2002), following the analysis of mtDNA sequences. On the other hand, the remaining genera, Citharichthys, Etropus and Syacium (Paralichthyidae I), which belong to the monophyletic group Cyclopsetta Chapleau, 1993), appeared related to the members of the families Bothidae and Achiridae analyzed in the present study.…”
Section: Phylogenetic Relationships Within Pleuronectiformesmentioning
confidence: 90%
See 3 more Smart Citations
“…Paralichthyidae appeared divided into two groups, one group was constituted by the genera Paralichthys and Pseudorhombus (Paralichthyidae II), which were soundly related to the members of the family Pleuronectidae which were analyzed. A relationship between species of Pleuronectidae and several paralichthyid genera had been previously suggested by Tinti et al (1999), and Berendzen and Dimmick (2002), following the analysis of mtDNA sequences. On the other hand, the remaining genera, Citharichthys, Etropus and Syacium (Paralichthyidae I), which belong to the monophyletic group Cyclopsetta Chapleau, 1993), appeared related to the members of the families Bothidae and Achiridae analyzed in the present study.…”
Section: Phylogenetic Relationships Within Pleuronectiformesmentioning
confidence: 90%
“…The position of Pleuronectiformes in relation to other major fish groups and the phylogenetic relationships within the order are still problematic. Most studies have been carried out based on morpho-anatomical characters (Hubbs, 1945;Lauder and Liem, 1983;Ahlstrom et al, 1984;Hensley and Ahlstrom, 1984;Chapleau, 1993), and only a few molecular phylogenetic analyses have been performed to date on this order (Vernau et al, 1994;Tinti et al, 1999;Berendzen and Dimmick, 2002).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To date, several genes of mtDNA have been used as molecular markers in the establishment of phylogenetic relationships among flatfishes, such as rRNA genes (Azevedo et al 2008), the cytochrome b gene (Borsa and Quignard 2001), the control region (Tinti et al 1999), and their combinations (Infante et al 2004). Nevertheless, it has been shown that the use of limited sequence data and markers with different evolving rates may cause errors in inferences of the evolutionary relationships among taxa.…”
Section: Introductionmentioning
confidence: 99%